Economic Determinants of Visitor Satisfaction: The Role of Social Media, Price Perception, and Service Quality at Villa Kintamani Gold View - Rahayu, Ira; Ayuni, Ni Made Sri (Yayasan Riset dan Pengembangan Intelektual, 2025)
Social media, price, and service quality are factors that can influence visitor satisfaction at Villa Kintamani Gold View. Reliable social media can have a positive impact on Villa Kintamani Gold View, ultimately benefiting the management through increased visitor satisfaction. Providing the best service quality to visitors will certainly lead to higher levels of visitor satisfaction. This study aims to determine the extent to which social media, price, and service quality affect visitor satisfaction. The research is causal in nature and employs a quantitative approach. The purposive sampling method was used to collect a sample of 85 respondents from the population. The findings indicate that social media, price, and service quality have a positive and significant impact on visitor satisfaction.